comparing the effectiveness of Bowen's family-based approach and Minuchin’s structural family therapeutic approach on improving communication patterns and reducing marital conflicts in women suffering from emotional divorce - Sabzevari , Parisa; Khoyinejad, Gholamreza; Saffarian Toosi , Mohammad Reza (Applied Family Therapy Journal (AFTJ), 2023)
Aim: Emotional divorce as a social harm is the first step in the divorce process and indicates the severity of marital conflicts originating from numerous factors such as the malfunctioning of couples' communication patterns. Hence, the present study aimed at comparing the effectiveness of Bowen's family-based approach and Minuchin’s structural family therapeutic approach on improving communication patterns and reducing marital conflicts in women suffering from emotional divorce. Method: The quasi-experimental research method was based on pretest-posttest along with a control group. The population included all the women suffering from marital conflicts referring to the Central Welfare Organization of Isfahan in the first three months of the year 1399. After sifting through the subjects, 45 samples were selected by simple random sampling and were categorized into two experimental and control groups. The tools applied in the research were the scale of communication patterns and marital conflicts. The samples of the experimental group attended the Bowen's and Minuchin’s family therapeutic training programs, but the control group did not receive any particular training. Finally, the data were analyzed at two levels of descriptive statistics (the Mean and the Standard Deviation) and inferential statistics (the analysis of Covariance and the analysis of Variance with multivariable frequent measuring) using SPSS software. Results: Findings revealed that both Bowen's and Minuchin’s therapeutic approaches can be effective on communication patterns and marital conflicts. In addition, a significant difference was noticed between the effectiveness of the two experimental groups (Bowen’s and Minuchin’s) on communication patterns of women suffering from emotional divorce, and the comparison of means suggested that family and structural therapy of Minuchin performed better. And finally, no significant difference was noticed between the effectiveness of the two experimental groups (Bowen’s and Minuchin’s) on marital conflicts in women suffering from emotional divorce, and only after lessening relationship with relatives, the structural effectiveness of Minuchin's approach proved to be better. Conclusions: Therefore, Bowen’s and Minuchin’s therapeutic approaches can both be helpful in reducing the rate of marital conflicts and improving the communication patterns of women suffering from emotional divorce, and consequently, reducing emotional divorce and increasing marital adjustments.